Next-level negotiating - Sheckells, Sara; Gallo, Amy; Rosette, Ashleigh Shelby; Mauro, Marisa (Ascent Audio, 2023)
Build trust-and create more value. Whether you're negotiating a salary, a deal with a supplier, or your workload, thoughtful preparation increases your confidence, resilience-and results. But it's not just numbers and strategies. Advocating for yourself, your team, and your business can feel personal, so you also need to manage the emotions that arise during the process. Next-Level Negotiating provides the research, advice, and practical tips you need to counter the harmful stereotypes about women and negotiation to communicate clearly who you are and what you need. Establish trust with your counterpart and face negotiations of any size with curiosity, creativity, and a collaborative mindset-all the essentials to successfully seal a deal. This book will inspire you to: set a clear target-and imagine alternatives; consider your counterpart's context and perspective; manage the emotions in the room; and strike a deal that works for you.
Online resource; title from title details screen (O'Reilly, viewed March 7, 2023)
Keywords: Negotiation in business; Women employees; Success in business; Psychology, Industrial; Négociations (Affaires); Personnel féminin; Succès dans les affaires; Psychologie du travail; Audiobooks; Livres audio